(untitled) (Web of Teachers: Inderscience Research, 2025)
Miniature art is a "specific method of painting in which the creation of small-scale works, especially depicting historical, cultural, and religious events, has traditionally been of great importance. Miniature art teaching in the process competence approach to students not only picture drawing technician sides to teach, but they for necessary was creative, professional and communicative competencies to develop provides.